2009
DOI: 10.3171/2008.12.spine08500
|View full text |Cite
|
Sign up to set email alerts
|

Foot drop due to lumbar degenerative conditions: mechanism and prognostic factors in herniated nucleus pulposus and lumbar spinal stenosis

Abstract: Object The aim of this study was to analyze the mechanism and prognostic factors of foot drop caused by lumbar degenerative conditions. Methods The authors retrospectively reviewed the charts of 28 patients with foot drop due to a herniated nucleus pulposus (HNP) or lumbar spinal stenosis (LSS), scoring between 0 and 3 on manual muscle testing for the tibialis anterior muscles. They analyzed the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 13 publications
3
54
0
Order By: Relevance
“…The former corresponds to pretibialis anterior muscle strength in the current study. Other predictors are age at surgery [6,7,16], herniated soft disc [7,12,13], and involvement of a single level [7]. In the current study, the two main predictors (pretibialis anterior strength and the duration of drop foot before surgery) were confirmed by the Bayesian network models as direct predictors.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The former corresponds to pretibialis anterior muscle strength in the current study. Other predictors are age at surgery [6,7,16], herniated soft disc [7,12,13], and involvement of a single level [7]. In the current study, the two main predictors (pretibialis anterior strength and the duration of drop foot before surgery) were confirmed by the Bayesian network models as direct predictors.…”
Section: Discussionsupporting
confidence: 56%
“…Predictors for residual drop foot in previous studies are varied, but the two main predictors have been preoperative motor weakness [1,3,6,12,16,17,21] and the duration of drop foot before surgery [2,3,7,16,17]. The former corresponds to pretibialis anterior muscle strength in the current study.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…On the other hand, Aono et al [11] reported that preoperative strength was a factor that most affected drop foot recovery following surgical intervention for patients with lumbar spinal degeneration. Similarly, Iizuka et al [12] demonstrated a significant association between prognosis and preoperative strength in drop foot patients with lumbar spinal stenosis. We thought that it was disadvantageous for recovery after surgery when the patient exhibited weaker muscle strength because this meant more severe damage to the spinal cord or nerve root.…”
Section: Discussionmentioning
confidence: 85%
“…Patients with signs of visceral involvement (e.g., bowel or bladder dysfunction), signs of severe radicular pain, acute motor axonal neuropathy, or chronic one but moderate-severe motor deficit, with spinal instability at dynamic flexedextended lumbar, x-rays were excluded [13][14][15].…”
Section: Methodsmentioning
confidence: 99%